A Organizaç\~ao das Naç\~oes Unidas e o objetivo de desenvolvimento sustentável 14: Desafios para o Brasil na década do oceano - Israel de Oliveira Andrade; Tarin Cristino Frota Mont'Alverne; Adriana I. B. Sá Leit\~ao Di Pasquale; Solange Teles da Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The United Nations Organization, after adopting the 2030 Agenda for Sustainable Development and establishing its seventeen goals, took a step further in its commitment to ocean conservation, declaring the Decade of Ocean Science for Sustainable Development (Ocean Decade), from 2021 to 2030. The actions undertaken in this area aim to guarantee that ocean science can support the States in order to achieve all the content of the 2030 Agenda, especially in what is related to the conservation of the ocean. Brazil, by assuming the commitments listed in the document launched during the United Nations Sustainable Development Summit, however, has faced a series of challenges related to the implementation of the Sustainable Development Goals (SDGs), in particular, SDG 14 "Life below water - conserve and sustainably use the oceans, seas and marine resources". Based on this premise, this article aims to demonstrate the urgent need to implement the SDGs, in particular SDG 14, to achieve the results of the Ocean Decade. To this end, at first, the association between the 2030 Agenda and the Ocean Decade is analyzed, noting the importance of the ocean for promoting sustainable development. The second section seeks to highlight the essentiality of SDG 14 for life below water, approaching the Ocean Decade as fundamental for actions in favor of conservation and sustainable use of the ocean in the present and future. And, complementing the present analysis, there is a discussion about the Brazilian strategies to reach the goals of SDG 14, considering in particular the role of the blue economy.
Keywords: F64; F68; G18; K33; Q56; Q01; 330; United Nations; Decade of Ocean Science for Sustainable Development; Sustainable Development Goals; SDG 14; Blue Amazon